Comparison of the application effect of LBL + PBL teaching method and CBL + PBL teaching method in nursing teaching of thyroid and breast surgery department. - ZHANG Jin; DOU Hongyan; ZHU Yanan (Journal of Clinical Nursing in Practice, 2023)
Objective To compare the application effect of lecture-based learning (LBL) + problem-based learing (PBL) and case-based learning (CBL) + PBL in nursing teaching of thyroid and breast surgery department. Methods From January 2021 to December 2021, the LBL + PBL teaching method was applied to the teaching of 47 nursing interns in the Department of Thyroid and Breast Surgery in the Affiliated Hospital of Xuzhou Medical University, and they were included in the LBL + PBL group. From January 2022 to December 2022, the CBL + PBL teaching method was applied to the teaching of 52 nursing interns, and they were included in the CLB + PBL group. The differences of examination scores, self-evaluation scores, and teaching satisfaction were compared between the two groups of nursing interns, and the effect of the two teaching modes were compared. Results The scores of theoretical examination, operation examination and comprehensive score in the LBL + PBL group were lower than those in the CBL + PBL group, with statistical significance (P < 0. 05). The scores of literature retrieval, autonomous learning, analysis and problem solving, communication, nursing work identification, and the ability to combine theory with practice in the LBL + PBL group were lower than those in the CBL + PBL group, with statistical significance (P < 0. 05). The total satisfaction rate of teaching in the LBL + PBL group was 80. 85%, which was lower than 96. 15% in the CBL + PBL group, and the difference was statistically significant (P < 0. 05 ). Conclusion Compared with LBL teaching mode, the teaching method of CBL combined with PBL is more effective in improving the theoretical and operational performance of nursing interns and increasing students' comprehensive ability. The nursing interns who receive CBL + PBL teaching have higher satisfaction with teaching.